Vision improvement in pilots with presbyopia following perceptual learning. (November 2018) - Sterkin, Anna; Levy, Yuval; Pokroy, Russell; Lev, Maria; Levian, Liora; Doron, Ravid; Yehezkel, Oren; Fried, Moshe; Frenkel-Nir, Yael; Gordon, Barak; Polat, Uri
Abstract: Israeli Air Force (IAF) pilots continue flying combat missions after the symptoms of natural near-vision deterioration, termed presbyopia, begin to be noticeable. Because modern pilots rely on the displays of the aircraft control and performance instruments, near visual acuity (VA) is essential in the cockpit. We aimed to apply a method previously shown to improve visual performance of presbyopes, and test whether presbyopic IAF pilots can overcome the limitation imposed by presbyopia. Participants were selected by the IAF aeromedical unit as having at least initial presbyopia and trained using a structured personalized perceptual learning method (GlassesOff application), based on detecting briefly presented low-contrast Gabor stimuli, under the conditions of spatial and temporal constraints, from a distance of 40 cm. Our results show that despite their initial visual advantage over age-matched peers, training resulted in robust improvements in various basic visual functions, including static and temporal VA, stereoacuity, spatial crowding, contrast sensitivity and contrast discrimination. Moreover, improvements generalized to higher-level tasks, such as sentence reading and aerial photography interpretation (specifically designed to reflect IAF pilots' expertise in analyzing noisy low-contrast input). In concert with earlier suggestions, gains in visual processing speed are plausible to account, at least partially, for the observed training-induced improvements.